The Consumer Protection Dynamics of Halal Products in Indonesia - Haryanti, Tuti; Miru, Ahmadi (Jambura Law Review, 2024)
Legal protection for consumers of halal products has occurred since the old order. At that time, halal regulations did not guarantee legal certainty. The state passed a regulation that specifically regulated the guarantee of halal products. However, it continues to change now. This research aims to analyze the development and direction of legal protection for consumers of halal products after enactment   of Halal Product Guarantee Law. This research was a normative domain using primary and secondary legal materials. Legal materials that have been collected were analyzed by explaining existing theories logically and systematically to obtain significant and scientific results. Furthermore, a transcript was carried out. The results of the research showed that the state has attempted to guarantee legal protection for consumers of halal products through the establishment of regulations. However, the regulation of the halal guarantee system continues to change and tends to be influenced by economic interests so the basic rights of consumers are not fulfilled. Therefore, the government needs to reform the legal system in protecting consumers of halal products based on the principle of balance of rights to provide a sense of justice, and benefit and guarantee legal certainty